Instagram Content Management for Interaction During the Covid 19 Pandemic - Sudiwijaya, Erwan; Sofyan, Nur (ARISTO, 2022)
Physical restrictions imposed during the pandemic stopped all concert activities, but @ykvvknd kept interacting with their followers. This study uses qualitative descriptive research method, where researchers collect data through field study techniques (interviews, observations, and document collection). These three data were collected through interviews. Our informant is the owner and manager of @ykvvknd content. Observations were made in the comment column for each @ykwknd content and document collection from articles in mass media. Authentic engagement is the only proven way for Instagram account managers to understand Gen Z, listen to them, and start forming relationships. Two-way communication among opinion leaders in their circle of friends is based on a high level of trust in opinion leaders.